Los procesos comunicativos en la Unidad Educativa “Poaló García Moreno”; Parroquia Poaló, Cantón Latacunga: Diseño de un manual bilingüe de los procesos educativos. - Cuyo Vega, María Ercilia (2017)
The present researching work was donde at "Poaló Garcia Moreno” Educative Unit. The main objective was to design a Bilingual Manual (Spanish-Kihwa) to the educommunicative processes. The instruments applied had relevant information on the topic, such as the surveys directed to the members of the educational community of the institution could prove the errors in the edu-communicative processes and correct them, because of, people don`t have enough knowledge about the Kichwa language. It was interesting to learn from the language of the people, in order to communicate with the students; the manager as leader should have looked for a strategy to recognize our language. The people in the educational processes carried out daily in the institution, since these processes had to be applied and put into practice by the managers and teachers of the educative unit. For this reason, it was considered significant, because, it allowed the administrative staff, teachers, students and parents have knowledge about the communicative processes in the mother tongue to the people and nationalities, in order to develop a proposal to solve educational processes for efficient and effective institutional performance. With the development and application to this manual; the institution members could count on a viable support document in their actions and daily administrative practice, in which the researched content covers updated and viable information that guided the development of the proposed topic and also served as a source of investigation for people who are interested in learning about the subject of the researched.